Analisis Perbandingan Jumlah Kuman Escherichia Coli dan Coliform pada Air Minum Isi Ulang di Wilayah Kerja Puskesmas Sungai Jingah Kota Banjarmasin Tahun 2022 - Sarifah Nur Annisa Fajar; Norfai Norfai; Zuhrupal Hadi (Jurnal Kesehatan Indonesia, 2022)
Water is a chemical compound that is very important for the life of living things on this earth. The function of water for life cannot be replaced by other compounds. The main use of water and very vital for life is as drinking water. Drinking water depot is an industrial business that processes raw water into drinking water and sells it directly to consumers. The purpose of this study was to compare the number of Escherichia coli and Coliform in refill drinking water depots in the working area of the Sungai Jingah Health Center, Banjarmasin City in 2022. This study used an analytical survey with a cross sectional approach. The population in this study were 49 refill drinking water depots in the working area of Sungai Jingah Health Center.sampling technique used was the total sampling. Based on statistical tests, it was found that the results of this test had a p-value of 0.882 (p-value > 0.05, so the data examined by the researcher did not have a significant difference). It is hoped that the owners and officers of refill drinking water depots can maintain and improve the quality of the drinking water they sell and pay attention to it.